2019
DOI: 10.1007/s13187-019-01571-w
|View full text |Cite
|
Sign up to set email alerts
|

Symptom Experience, Management, and Outcomes According to Race and Social Determinants Including Genomics, Epigenomics, and Metabolomics (SEMOARS + GEM): an Explanatory Model for Breast Cancer Treatment Disparity

Abstract: Even after controlling for stage, comorbidity, age, and insurance status, black women with breast cancer (BC) in the USA have the lowest 5-year survival as compared with all other races for stage-matched disease. One potential cause of this survival difference is the disparity in cancer treatment, evident in many population clinical trials. Specifically, during BC chemotherapy, black women receive less relative dose intensity with more dose reductions and early chemotherapy cessation compared with white women.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 105 publications
0
17
0
Order By: Relevance
“…Given that this study evaluated a very limited number of social determinants of health, future research needs to explore additional characteristics (e.g., neighborhood, food security, environmental exposures). 52 While previous studies found an association between older age and higher levels of CRCI, as well as sleep disturbance, 4,7,8 patients in our High class were more likely to be younger. Of note, our finding is consistent with a study by the developers of the AFI who noted that younger individuals may react more strongly to small cognitive changes, while older individuals may have lower expectations, having adapted to alterations in cognition that accompany normal aging.…”
Section: Demographic and Clinical Characteristicsmentioning
confidence: 51%
“…Given that this study evaluated a very limited number of social determinants of health, future research needs to explore additional characteristics (e.g., neighborhood, food security, environmental exposures). 52 While previous studies found an association between older age and higher levels of CRCI, as well as sleep disturbance, 4,7,8 patients in our High class were more likely to be younger. Of note, our finding is consistent with a study by the developers of the AFI who noted that younger individuals may react more strongly to small cognitive changes, while older individuals may have lower expectations, having adapted to alterations in cognition that accompany normal aging.…”
Section: Demographic and Clinical Characteristicsmentioning
confidence: 51%
“…It also stands to reason that increasing time from diagnosis and requirement for additional treatment lines is associated with increasing symptom burden. Multiple studies have demonstrated disparities in cancer outcomes among nonwhite patients [19][20][21][22] and this is suggested here. Further investigation of this is warranted in this setting as well.…”
Section: Discussionmentioning
confidence: 78%
“…Related factors such as socioeconomic status, community behaviors towards health, and access to health care are common discussion points with regard to race and pain. 93,94 Interestingly, this association between race and NP is not consistent in the literature. In studies of chemotherapy-induced peripheral neuropathy, race is not a significant predictor of neuropathy.…”
Section: Discussionmentioning
confidence: 80%
“…However, environment, rather than genetic predisposition, is believed to play a bigger role in this relationship. Related factors such as socioeconomic status, community behaviors towards health, and access to health care are common discussion points with regard to race and pain 93,94 . Interestingly, this association between race and NP is not consistent in the literature.…”
Section: Discussionmentioning
confidence: 97%